Populism, Cognitivism, and the Critique of Reason - Caviglia, Alessandro (2021)
The present work seeks to offer a philosophical approach to the phenomenon of populism, an approach that differs from the one that comes from the social sciences because it offers critical and normative aspects. In this sense, the anticognitivism and dogmatism of the populist proposals will be criticized and the Kantian ideal of the Kingdom of ends will be opposed to the substantive concept of the people offered by populist theorists such as Ernesto Laclau.